Analyzing Real World Outcomes, Identifying Key Management Challenges, and Uncovering Distinct Patient Subgroups in Amblyopia Treatment Through a Large Scale Retrospective Database Study - Talia N. Shoshany; Cahyatih Kumandang (Takaza Innovatix Labs Ltd., 2024)
This study aims to evaluate real-world outcomes in amblyopia treatment, identify key challenges in long-term management, and characterize distinct patient subgroups using a large retrospective dataset of pediatric patients at a tertiary eye center. A total of 2,044 patients were analyzed using standardized IRIS7 and IRIS50 success criteria. Risk factors for treatment dropout were examined using multivariable logistic regression, and a predictive risk score was developed to estimate the probability of loss to follow-up (LTFU). The findings revealed that 71% and 81% of patients met success under IRIS7 and IRIS50 criteria, respectively. However, 23% were lost to follow-up, with six factors—such as lack of insurance, older age, and prior occlusion—predicting discontinuation. AUC for the LTFU risk calculator was 0.68, indicating moderate predictive ability. Additionally, patients with asymmetric bilateral amblyopia demonstrated comparable improvement with glasses alone versus early occlusion, suggesting a potential revision in treatment protocols. These findings underscore the importance of personalized amblyopia care, predictive follow-up tools, and standardized outcome measures to improve adherence and visual outcomes.